Planning of Territorial-Production Structure of Russia’s Fuel-and-Energy Complex - Viktor Dmitrievich Kalashnikov (Prostranstvennaâ Èkonomika, 2005)
Economic grounds of formation of the production and territorial structure of the Russian fuel-and-energy complex are considered, characteristics of the centralized planning models of the power supply systems in the USSR economy are studied in view of various concepts of economic regions. Issues of transformation of the mechanisms of spatial decisions’ elaboration in the Russian power sector during crisis and post-crisis periods are discussed